Investigation of interaction between solitary wave and two submerged rectangular obstacles. (1st October 2021) - Ghafari, Ashkan; Tavakoli, Mohammad Reza; Nili-Ahmadabadi, Mahdi; Teimouri, Kowsar; Kim, Kyung Chun
Abstract: The performance of coastal breakwaters in reducing wave height and energy is an important problem. This paper presents an experimental and numerical investigation of solitary wave interaction with two submerged rectangular obstacles. White light and particle image velocimetry (PIV) techniques were utilized to study the free surface profile of a solitary wave and flow field in an experimental procedure. The PIV test results revealed that two clockwise vortices are generated between and after the two obstacles, and the white light test results showed that three phenomena of wave breaking, crest-crest exchange, and air-water mixing occur in the solitary wave passage over the two obstacles. A transient two-dimensional numerical model was used to study solitary wave interaction with two rectangular obstacles. The numerical model was validated with experimental results in terms of free surface profile, velocity fields, and velocity profiles. Using this model, the effects of obstacles height and distance were investigated. The numerical results showed that when increasing the height of the obstacles, the drag force applied on the obstacles, the strength of vortices, the energy loss, and the height reduction of the solitary wave increased. The presence of the second obstacle and wave breaking occurrence constrain the movement of vortices and cause a negative drag coefficient on the obstacles in some cases. The energy loss, the height reduction of the solitary wave, and the strength of the vortex generated between the obstacles increased as the distance of the obstacles increased up to S/L = 1.5. In contrast, the strength of the vortex generated after the second obstacle was decreased by increasing the distance of two obstacles. Highlights: This paper investigates interaction of solitary wave with two submerged rectangular obstacles experimentally and numerically. White light and PIV techniques were utilized to study the free surface profile of a solitary wave and flow field. Increasing the obstacles height increased the drag force, the strength of vortices, and the solitary wave height reduction. The strength of the vortex generated after the second obstacle was decreased by increasing the distance of two obstacles.